Public Understanding and Expectations of Digital Health Evidence Generation: Focus Group Study - Paulina Bondaronek; Jingfeng Li; Henry W W Potts (JMIR Formative Research)
Abstract BackgroundThe rapid proliferation of health apps has not been matched by a comparable growth in scientific evaluations of their effectiveness, particularly for apps available to the public. This gap has prompted ongoing debate about the types of evidence necessary to validate health apps, especially as the perceived risk level varies from wellness tools to diagnostic aids. The perspectives of the general public, who are direct stakeholders, are notably underrepresented in discussions on digital health evidence generation. ObjectiveThis study aimed to explore public understanding and expectations regarding the evidence required to demonstrate health apps’ effectiveness, including at varying levels of health risk. MethodsA total of 4 focus group discussions were held with UK residents aged 18 years and older, recruited through targeted advertisements to ensure demographic diversity. Participants discussed their views on evidence requirements for 5 hypothetical health apps, ranging from low-risk wellness apps to high-risk diagnostic tools. Focus groups were moderated using a structured guide, and data were analyzed using reflexive thematic analysis to extract common themes. ResultsA total of 5 key themes were established: personal needs, app functionality, social approval, expectations of testing, and authority. Participants relied on personal experiences and social endorsements when judging the effectiveness of low-risk digital health interventions, while making minimal reference to traditional scientific evidence. However, as the perceived risk of an app increased, there was a noticeable shift toward preferring evidence from authoritative sources, such as government or National Health Service endorsements. ConclusionsThe public have a preference for evidence that resonates on a personal level, but also show a heightened demand for authoritative guidance as the potential risk of digital health interventions increases. These perspectives should guide developers, regulators, and policy makers as they balance how to achieve innovation, safety, and public trust in the digital health landscape. Engaging the public in evidence-generation processes and ensuring transparency in app functionality and testing can bridge the gap between public expectations and regulatory standards, fostering trust in digital health technologies.